How promising are HIV-1-based virus-like particles for medical applications - Martins, Sofia A.; Santos, Joana; Silva, Rúben D. M.; Rosa, Cátia; Cabo Verde, Sandra; Correia, João D. G.; Melo, Rita (Frontiers in Cellular and Infection Microbiology, 2022)
New approaches aimed at identifying patient-specific drug targets and addressing unmet clinical needs in the framework of precision medicine are a strong motivation for researchers worldwide. As scientists learn more about proteins that drive known diseases, they are better able to design promising therapeutic approaches to target those proteins. The field of nanotechnology has been extensively explored in the past years, and nanoparticles (NPs) have emerged as promising systems for target-specific delivery of drugs. Virus-like particles (VLPs) arise as auspicious NPs due to their intrinsic properties. The lack of viral genetic material and the inability to replicate, together with tropism conservation and antigenicity characteristic of the native virus prompted extensive interest in their use as vaccines or as delivery systems for therapeutic and/or imaging agents. Owing to its simplicity and non-complex structure, one of the viruses currently under study for the construction of VLPs is the human immunodeficiency virus type 1 (HIV-1). Typically, HIV-1-based VLPs are used for antibody discovery, vaccines, diagnostic reagent development and protein-based assays. This review will be centred on the use of HIV-1-based VLPs and their potential biomedical applications.